Prilagoditvene spremembe v ramenskem sklepu športnika metalca - Cunder, Katarina (Rehabilitacija (Ljubljana), 2008)
Adaptational changes that develope due to repetitional stress placed upon the glenohumeral joint in the typical biomechanical manner can be found in the majority of the overhead athletes. The most popular overhead sports in central Europe are handball, volleyball and tennis and in lesser extent waterpolo and baseball. Typical strike or throw starts in extreme external rotation and abduction in the late cocking phase and progresses through extension of the elbow to the internal rotation and adduction of the shoulder in deceleration phase, but there are sport-specific differences. First changes that we observe in young overhead athletes are decreased internal rotation and increased external rotation range of motion in abducted shoulder. Until recent years, symptomatic glenohumeral internal rotation deficit (GIRD of more than 25°) together with parameters of malposition and dyskinesis of the SICK scapula syndrome were the most important prognostic tools for evaluating shoulder at risk and an important lead for training and rehabilitation programes, but the true prognostic value of symptomatic GIRD has been questioned in some recent studies. Nevertheless, GIRD remains the earliest sign of posteroinferior joint capsule tightness, which is the first in the cascade of events that lead to disabled overhead shoulder. Recently, many authors belive that bone adaptations such as humeral retroversion that take place in the shoulder of an infant overhead athlete may also have an important role in glenohumeral internal rotation deficit and in the developing of the shoulder at risk.
Keywords: športniki; ramenski sklep; spremembe